Varicocelectomy in Patients with Non-obstructive Azoospermia - Cevahir Özer; Mehmet Reşit Gören; Ümit Gül; Tahsin Turunç; Sezgin Güvel (Journal of Urological Surgery)

(untitled)
Objective:We evaluated the outcomes of varicocelectomy in men with non-obstructive azoospermia (NOA) and a palpable varicocele.Materials and Methods:We retrospectively evaluated 25 male patients with NOA having a palpable varicocele, between May 2006 and December 2018. Age, duration of infertility, testicular volume, grade and side of varicocele, varicocelectomy technique, and serum follicle-stimulating hormone, serum luteinizing hormone and serum testosterone levels were analyzed.Results:The mean age of the patients was 30.68±3.91 years. Of the 25 patients, 5 (20%) had motile sperm in the ejaculate in the postoperative semen analysis. There were no predictive factors affecting the appearance of the sperm in the ejaculate.Conclusion:Varicocelectomy should be considered a treatment option for men with NOA having a palpable varicocele.